ANALISIS FLUKTUASI ARUS LALU LINTAS KOTA PALU (Studi Kasus: Kota Palu Bagian Barat) - Kasan, Muhammad (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2011)
Traffic flow is due to the interaction between the system of activities with transport network system inthe form of movement of vehicles on the highway. This type of land use led to a different traffic flowfluctuations every street throughout the day.The purpose of this study was to determine fluctuations in traffic, timing and magnitude of peak hours ,percentage of traffic is covered by long observation of traffic flows.Traffic flow data collection done on location, KH. Wahid Hashym Street, Sis Al Jufri Street andPangeran Diponegoro street, West Palu. The type of data on the study include primary data andsecondary data. The primary data include the volume of data traffic flow on roads. Secondary dataincludes data of road networks, land use maps, maps of the Palu City. The primary data werecollected with a traffic volume survey on Monday – Thursday and Saturday.The result of the study was to found that the secondary arterial road network system, the peak hourson weekdays occurred at 4:00 p.m. to 5:00 p.m. with the traffic flow of 2168 pcu /h, at the weekendoccurred at 08:00 to 09:00 with traffic flow for 2330 pcu/h. At the secondary collector road networksystem, the peak hours on weekdays occur in at 07.00 - 08.00, the traffic flow of 1928 pcu/hour, atthe weekend occurred at 4:00 p.m. to 17:00, the traffic flow of 1638 pcu h.The results of fluctuation analysis of traffic flow on weekdays for a secondary arterial roads was foundthat if the survey was conducted for 16 hours then the time most remains are 6:00 a.m. to 10:00 p.m.,with the volume of traffic is 92% covered. When the survey was conducted for 12 hours then the besttime is 07:00 to 19:00, traffic volume is 73.42% covered. If the volume of traffic surveys carried out for 8hours, the best time is at 11:00 to 19:00, traffic volume data covered is 48.68%.The results on the secondary collector streets on working hours to get that when the traffic volumesurvey for 16 hours then the best time is 06:00 to 22:00 with traffic volume covered 92.34%. . When thesurvey was conducted for 12 hours then the best time is 07:00 to 19:00, traffic volume is 77.02%covered. . If the volume of traffic surveys carried out for 8 hours, the best time is at 07:00 to 15:00,traffic volume data covered is 54.15%.